A comparison of handover communication in NHS and military emergency care. (2nd April 2020) - Slope, Rowena; Pope, Catherine; Crouch, Robert; Bernthal, Elizabeth MM
Abstract : Background: There is a gap in the literature comparing communication during handover between military and NHS emergency care settings. Objectives: This study aimed to explore differences in handover communication in the NHS and the military, and to understand how paramedics manage the transition between settings. Design: This was a qualitative study for which 13 paramedics were interviewed. It focused on handover communication in NHS emergency care settings and Camp Bastion Hospital, Afghanistan. Methods: Interviews were conducted with regular and reservist paramedics serving in the Royal Air Force who had undertaken a deployment with the Medical Emergency Response Team. Semi-structured interviews were recorded, transcribed, coded and subjected to a thematic analysis. Results: Three principal themes were identified: differences between handover communication; standardisation; and the challenge of transition. Conclusion: Participants were most concerned about standardisation. Transition theory and resilience may account for the difficulties encountered when transitioning between different care settings.